ESG Communication Analysis in Building Stakeholder Trust in Public Banking Companies in Indonesia Amid the Greenwashing Issue - Zidnal Falah (International Journal of Social Research, 2025)
This study aims to analyze Environmental, Social, and Governance (ESG) communication in building stakeholder trust in public banking companies in Indonesia amid the increasing issue of greenwashing. The research uses a qualitative approach with a descriptive design of a case study. Data was collected through in-depth interviews with management, questionnaires to licensed employees, as well as observations of sustainability reports, annual reports, official company websites, press releases, and corporate social media. The results show that ESG communication has an important role in shaping stakeholder trust, especially when messages are conveyed in a transparent, consistent, accountable, and supported by tangible evidence of implementation. The interview's findings show that management views ESG communication as a strategic part of a company's reputation and legitimacy, but still faces challenges in maintaining a fit between sustainability narratives and business practices. The results of the questionnaire showed that transparency and accountability received high ratings, while the evidence aspect of the program was still relatively low. The results of the observation also confirm that the intensity of ESG communication has not always been followed by adequate depth of information. This study concludes that credible, data-driven, and integrated ESG communication is an important factor in strengthening stakeholder trust and minimizing the risk of perceived greenwashing in public banking companies in Indonesia.